Pengendalian Kualitas pada Proses Produksi Air Bersih di PT Dumai Tirta Persada - Marbun, Novri Jenita; Suarlin, John; Kurnianti, Devi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
PT Dumai Tirta Persada is a business engaged in the clean water treatment system to manage SPAM (Drinking Water Supply System) facilities in Dumai City. Currently, PT Dumai Tirta Persada has two Water Treatment Plants (WTP) with a maximum production capacity of 200 liters/second, where, based on interviews, the raw water used comes from the river, which often has fluctuating conditions such as pH, TDS (Total Dissolved Solids), turbidity, and color that sometimes vary between high and low, thus significantly affecting the quality of the clean water produced to meet the quality standards. The purpose of this research is to identify the factors that influence and the factors that are prioritized for improving water quality at PT Dumai Tirta Persada. The type of research used is quantitative, with data collection techniques for clean water parameters to monitor changes and fishbone questionnaires to identify the factors causing deviations in water quality. Based on the results of parameter data processing using X and R control charts, it was found that the control limits for each parameter have out-of-control capability, with the contributing factors being human, method, material, machine, and environment, with the main factor being the human factor. So it can be concluded that an evaluation of the workers needs to be conducted through socialization with the hope that the workers will perform their tasks better, thereby maintaining the quality of the water.